H60 Economic burden of Huntington's disease: targeted literature review to inform gene therapy economic evaluations in the US. (12th September 2022) - Munetsi, L; Malik, S; Guzauskas, G; Rodriguez-Santana, I; Ali, T; Ratsch, S; Zhang, F
Abstract : Background: Novel gene therapies (GTx) development raises important cost-effectiveness and affordability questions. As Huntington's disease (HD) is rare, evidence to inform GTx economic evaluations (EE) is scarce. Aims: We performed a targeted literature review to identify evidence on the economic burden and impact of HD to inform EE of GTx in HD. Methods: This study was conducted on MEDLINE and other databases via an inclusion/exclusion criterion identifying studies relating to HD, costs, healthcare resource utilisation (HRU), and burden of illness (BOI). Results: We identified 861 studies of which 15 were US-based BOI studies. A majority of these (12/15) focused on the healthcare payer perspective, while 3/15 studies mentioned societal costs. Eight out of fifteen publications provided data with HD stratification (early (ES), mid (MS) and advanced stages (AS)). HRU and direct annual costs per patient increased in line with HD stage from $3, 612 to $20, 475 for ES, from $11, 808 to $29, 733 for MS, and from $22, 116 to $66, 070 for AS. One study employed TFC-score stratification using a societal perspective. Another study highlighted societal resource utilisation of 6.28 caregiver hours/day. Conclusions: Our findings highlight substantial economic burden due to HD., However, most studies focused on direct medical costs, omitting indirect costs. HD stratification was typically based on HRU type as a disease severity marker, rather than employing validated tools such as TFC, which may not provide a true reflection of HD health state residency. This review highlights the paucity of country specific societal values in appropriately informing future US EEs.